SPEECH ACTS IN POLICE INVESTIGATIVE INTERVIEWS - Ricky Drimarcha Barus; Amrin Saragih; Thyrhaya Zein (Universitas Negeri Medan, 2018)
This study aimed at exploring the speech acts in police investigative interviews. The objectives of the study were to discover, to explain how types of speech acts used by the interviewers and interviewees in the police investigative interviews on Michael Brown’s case and to elaborate the reasons. This research applied descriptive qualitative method. The data were the utterances gathered from the interviewers and the interviewees in two different investigative interviews. They were then analyzed by using Searle’s Speech Acts theory. The findings revealed that the five types of speech acts, namely representative, directive, commissive, expressive and declarative were found in the first investigative interview. However, declarative was not found in the second investigative interview. The most dominant type from the two investigative interviews was representative speech act. The most dominant speech act performed by the detectives and special agents as the interviewers was directive speech act. The most dominant speech act performed by the suspect and the witness as the interviewee was representative speech act. The interviewers and interviewees performed them in two ways, direct - literal way and indirect - literal way, in which the direct - literal way was the most dominant one. The main reason why the interviewers performed directive speech act in the form of questioning, clarifying questioning and confirming questioning was to find facts and information. On the other hand, the interviewees performed the representative speech act in order to inform, explain, describe, affirm or deny. The direct - literal way was dominantly performed because all the participants want to avoid misunderstanding through ambiguous words or sentences since the investigative interviews are serious things.Keywords: interview, investigative interviews, speech acts